The Implementation of the Sociopreneur Strategy in the Role of Raharjo Village Owned Enterprises (BUMDES) in the Development of the Strawberry Barn Tourist Village, Batu City - Desembrianita, Eva; Maruf, Nirwanto; Wijayanti, Tri Cicik; Wasik, Zainul; Jumadi, Jumadi (Budapest International Research and Critics University, 2021)
The purpose of this study is to investigate the sociopreneur-based business strategies are implemented by the manager of Raharjo BUMDes in developing a tourist village in the